Degradation systems in heart failure. (July 2015) - Nishida, Kazuhiko; Yamaguchi, Osamu; Otsu, Kinya
Abstract: Heart failure is a complex clinical syndrome that results from any structural or functional impairment of ventricular filling or the ejection of blood, and is a leading cause of morbidity and mortality in industrialized countries. The mechanisms underlying the development of heart failure are multiple, complex and not well understood. Cardiac mass and its homeostasis are maintained by the balance between protein synthesis and degradation, and an imbalance is likely to result in cellular dysfunction and disease. The protein degradation systems are the principle mechanisms for maintaining cellular homeostasis via protein quality control. Three major protein degradation systems have been identified, namely the calpain system, autophagy, and the ubiquitin proteasome system. Proinflammatory mediators involve the development and progression of heart failure. DNA and RNA degradation systems play a critical role in regulating inflammation and maintaining cellular homeostasis mediated by damaged DNA clearance and posttranscriptional regulation, respectively. This review discusses some recent advances in understanding the role of these degradation systems in heart failure. Highlights: The protein degradation systems maintain cellular homeostasis. Calpains are required for plasma membrane maintenance. Autophagy is a cardioprotective mechanism against external stress. DNA and RNA degradation systems regulate inflammation. Mitochondrial DNA that escapes from autophagy causes inflammation and heart failure.